2012
DOI: 10.1111/j.1939-0025.2011.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk for arrest: The role of social bonds in protecting foster youth making the transition to adulthood.

Abstract: This study examines a sample of foster youth at the onset of the transition to adulthood and explores how social bonds are related to the risk of arrest during adulthood. Drawing from official arrest records, event history models are used to examine the time to arrest. Because individuals may be at risk for different types of crime, competing risk regression models are used to distinguish among arrests for drug-related, nonviolent, or violent crimes. Between the ages of 17–18 and 24, 46% of former foster youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 51 publications
(56 reference statements)
3
63
1
Order By: Relevance
“…), the contribution of parental support to their lives afterwards is not clear (Cusick et al . ). The current findings emphasize that for at least one year after the young people leave care, good relationships with their mothers, despite any complexity, contribute positively to their lives.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…), the contribution of parental support to their lives afterwards is not clear (Cusick et al . ). The current findings emphasize that for at least one year after the young people leave care, good relationships with their mothers, despite any complexity, contribute positively to their lives.…”
Section: Discussionmentioning
confidence: 97%
“…However, a recent analysis of data from the longitudinal Midwest study of Cusick et al . () found only weak relationship between perceived social support and the risk for arrest among young people who aged out of care, which could indicate that social support may not always be enough.…”
Section: Social Support For Young People Who Aged Out Of Carementioning
confidence: 97%
See 1 more Smart Citation
“…6,48,[57][58][59] In adulthood, elevated physical, mental health, and substance use risks persist, in addition to increased rates of low academic achievement, unemployment, low income, disability, poverty, lack of health insurance, homelessness, and engagement in illegal behavior. 56,[60][61][62][63][64][65] Despite guidelines for screening and evaluating youth entering the child welfare system for behavioral health needs, well-documented high rates of behavioral health needs and multiple reports of disproportionately high rates of mental health use, and expenditures by youth involved with the child welfare system, significant unmet or underserved behavioral health needs exist. The National Surveys of Child and Adolescent Well-Being (NSCAW), 2 national longitudinal studies of youth and families referred to the child welfare system, provide valuable information regarding behavioral health needs and underuse of services.…”
Section: Principle 6 Clinicians Should Involve Biological and Fostermentioning
confidence: 99%
“…In addition, several studies have found that approximately a third of former foster care youth have been arrested after leaving foster care (Barth, 1990; Courtney et al, 2005; Havalchak, White, & O’Brien, 2008). Using data from the Midwest Study (n=728), Cusick, Havlicek, and Courtney (2012) found that among young adults transitioning out of foster care, arrests were evenly distributed among violent, property and drug offenses.…”
Section: Introductionmentioning
confidence: 99%